2001
DOI: 10.1016/s0960-9822(01)00065-3
|View full text |Cite
|
Sign up to set email alerts
|

PTEN regulates the ubiquitin-dependent degradation of the CDK inhibitor p27KIP1 through the ubiquitin E3 ligase SCFSKP2

Abstract: The PTEN tumor suppressor acts as a phosphatase for phosphatidylinositol-3,4,5-trisphosphate (PIP3) [1, 2]. We have shown previously that PTEN negatively controls the G1/S cell cycle transition and regulates the levels of p27(KIP1), a CDK inhibitor [3, 4]. Recently, we and others have identified an ubiquitin E3 ligase, the SCF(SKP2) complex, that mediates p27 ubiquitin-dependent proteolysis [5-7]. Here we report that PTEN and the PI 3-kinase pathway regulate p27 protein stability. PTEN-deficiency in mouse embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
167
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(179 citation statements)
references
References 11 publications
10
167
0
1
Order By: Relevance
“…The balance between PI3K and PTEN has also been shown to regulate the expression level of SKP2, a ubiquitin E3 ligase that acts as a component of the SCF ligase. The expression levels of PTEN and SKP2 are inversely related (Mamillapalli et al, 2001). However, SKP2 appears to be highly selective and only targets a handful of proteins involved in cell cycle regulation, such as p27 Kip1 and p21 CIP1 (Reed, 2003), and so is unlikely to play a significant role in regulating the expression levels of our target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between PI3K and PTEN has also been shown to regulate the expression level of SKP2, a ubiquitin E3 ligase that acts as a component of the SCF ligase. The expression levels of PTEN and SKP2 are inversely related (Mamillapalli et al, 2001). However, SKP2 appears to be highly selective and only targets a handful of proteins involved in cell cycle regulation, such as p27 Kip1 and p21 CIP1 (Reed, 2003), and so is unlikely to play a significant role in regulating the expression levels of our target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Akt enhances the degradation of p27 by the proteasome-dependent pathway by upregulating SKP2 mRNA levels. SKP2 is a key component of the SCF/SKP2 ubiquitin ligase that mediates p27 degradation in a cyclin E/CDK2 dependent phosphorylation (Hara et al, 2001;Mamillapalli et al, 2001;Pagano et al, 1995). Previously it was shown that Akt-mediated phosphorylation of p27 at thr-157 also causes the relocation of p27 to the cytoplasm, thus relieving the nuclear substrates from p27 inhibition and enhancing the cell cycle progression (Shin et al, 2002).…”
Section: Pi3-k/akt Pathway and Cell Cycle Progressionmentioning
confidence: 99%
“…It has been shown that PTEN induces accumulation of the p27 protein at a post-transcriptional level (Mamillapalli et al, 2001). In contrast, PTEN-induced downregulation of vascular endothelial growth factor (VEGF) results from decreased activity of the VEGF promoter (Koul et al, 2002;Gomez-Manzano et al, 2003).…”
Section: Pten Inhibits Igf-ir Precursor Translation In Prostate Cancementioning
confidence: 99%